Exploring Circularity: A Review to Assess the Opportunities and Challenges to Close Loop in Nepali Tourism Industry - Aryal, Chandramani (Journal of Tourism & Adventure, 2020)
Tourism is one of the important sectors in Nepali economy and gains high priority from the government sector as well owing to its contribution in the economic, social and environmental front. Despite these benefits, the tourism sector comes with negative externalities, providing rationality for shift towards a more sustainable approach. Despite this, the circular economy is yet to gain recognition, both at the academic and industrial level in Nepal. Thus, this article aims to fulfill that gap by introducing the concept of circular economy, application of circular economy to the tourism industry and barriers for their implementation in Nepal. In different parts of the world, transition towards circular economy, which integrates the concepts of restorative economy, sharing economy and service economy, from the linear one have been identified as an approach for sustainable economic development. Innovation and application of the 4R principles have been identified as the key to the shift towards the circular economy. Innovation implies the use of new, innovative and more durable products, innovation in the production process and innovative organizational process. Innovation of business models, reduction of the resources used, reuse of the old products thereby reducing the demand for the new ones and recycling of waste products generated are some of the strategies of the circular economy that are applicable to the tourism industry. As Nepali tourism sectors are largely based on take-use-dispose form, they are unsustainable. Circular economy can address the problem associated with the tourism sector there by making the sector sustainable. But, adaptation of circular tourism is hindered mainly by financial and knowledge constraints. The study is expected to introduce and initiate academic discourse about circular tourism in Nepal.